Media attention and agency costs: Evidence from listed companies in China. (June 2022) - An, Yunbi; Jin, Han; Liu, Qingfu; Zheng, Kaixin
Highlights: We analyze the effects of media attention on agency costs. Negative media coverage helps reduce agency costs in Chinese firms. Negative media reports can enhance the quality of information disclosure. Negative media reports induce regulatory authorities to impose penalties. Negative media reports cannot motivate managers to correct their behaviors by affecting their reputation. Abstract: This paper analyzes the effects of media attention on agency costs based on data on Chinese listed companies. We find that in China, media with a higher degree of independence tend to cover more negative corporate news. In addition, negative media coverage better captures the intensity of media attention, and significantly reduces agency costs in Chinese firms. We further demonstrate that negative media coverage plays an important role in improving the quality of information disclosure and inducing the intervention of regulatory authorities, thereby mitigating agency conflicts in listed companies. However, negative media coverage cannot effectively push corporate managers to correct their behaviors by affecting their reputation. Finally, compared with non-state-owned enterprises (non-SOEs), SOEs receiving negative news reports are less likely to improve the quality of their information disclosure, more likely to be punished by regulatory authorities, and less likely to be influenced by managerial reputation concerns.